Elongator promotes neuritogenesis via regulation of tau stability through acly activity - Michal Shilian; Aviel Even; Hila Gast; Laurent Nguyen; Miguel Weil (Frontiers in Cell and Developmental Biology, 2022)
The six subunits (Elp1 to Elp6) Elongator complex promotes specific uridine modifications in tRNA’s wobble site. Moreover, this complex has been indirectly involved in the regulation of α-tubulin acetylation in microtubules (MTs) via the stabilization of ATP-Citrate Lyase (Acly), the main cytosolic source of acetyl-CoA production in cells, a key substrate used for global protein acetylation. Here, we report additional evidence that Elongator activity is important for proper cytoskeleton remodeling as cells lacking expression of Elp1 show morphology impairment; including distinct neurite process formation and disorganization and instability of MTs. Here, we show that loss of Elongator results in a reduction of expression of the microtubule associated protein Tau (MAPT). Tau, is a well-known key MT regulator in neurons whose lysines can be competitively acetylated or ubiquitylated. Therefore, we tested whether Tau is an indirect acetylation target of Elongator. We found that a reduction of Elongator activity leads to a decrease of lysine acetylation on Tau that favors its proteasomal degradation. This phenotype was prevented by using selective deacetylase or proteasomal inhibitors. Moreover, our data demonstrate that Acly’s activity regulates the mechanism underlying Tau mediated neurite morphology defects found in Elp1 KD since both Tau levels and neurites morphology are restored due to Acly overexpression. This suggests a possible involvement of both Tau and Acly dysfunction in Familial Dysautonomia (FD), which is an autosomal recessive peripheral neuropathy caused by mutation in the ELP1 gene that severely affects Elp1 expression levels in the nervous system in FD patients in a similar way as found previously in Elp1 KD neuroblastoma cells.